Educating the Ontological Model of Intellectual Capital Devel-opment Using the Method “Categorial Series” - Nedoluzhko, Olga V. (2020)
The development of intellectual capital at the macro- and mesoscale is the main tool for the transition of the economy to a progressive sixth technological mode, and at the level of an individual organization it ensures its stable position and high competitiveness in the market. However, training and educating its applications are of a great importance. A prerequisite for an effective implementation of this process is the formation of a systemic idea about the phenomenon of intellectual capital, the composition of its elements, the sequence of stages and the necessary conditions for its formation. To solve this problem, the article proposes to use a categorical-system methodology, in particular, the method of “categorical series”. Using the method, the analysis and a comprehensive description of intellectual capital development within the categories of the subject area is performed. The main characteristics of cognitive activity at various stages of intellectual capital development are determined. An ontological model of intellectual capital, which is based on the comparison of concept pairs in accordance with the nature of the contradictions developing between them, is proposed. Application of the model makes it possible to determine some promising areas for the development of intellectual capital, taking into account available resources, as well as to formulate the requirements for the composition of resources to obtain a certain type of intellectual capital. A further prospect of the obtained model use is the development of a full-fledged scientific theory of intellectual capital, including, in addition to its constituent element description, the determination of their formation stage sequence and the mechanism of their interaction. The use of this theory will make it possible to implement effective managerial influences on intellectual capital in order to increase the level of its systemic and organizational complexity. The presented results can be applied in legislative activity and in the development of program documents of the Government and the constituent entities of the Federation aimed at the Russian economy change.